A new integration model of the calcium looping technology into coal fired power plants for CO2 capture. (1st May 2016) - Ortiz, C.; Chacartegui, R.; Valverde, J.M.; Becerra, J.A.
Highlights: A CaL-CFPP (coal fired power plant) integration model is proposed and efficiency penalty is estimated. Carbonation in the diffusion stage is considered to predict the capture efficiency. Low efficiency penalty may be achieved by operating with longer particles' residence time. Simulation results show that the energy penalty ranges between 4% and 7% points. Abstract: The Ca-Looping (CaL) process is at the root of a promising 2nd generation technology for post-combustion CO2 capture at coal fired power plants. The process is based on the reversible and quick carbonation/calcination reaction of CaO/CaCO​3 at high temperatures and allows using low cost, widely available and non toxic CaO precursors such as natural limestone. In this work, the efficiency penalty caused by the integration of the Ca-looping technology into a coal fired power plant is analyzed. The results of the simulations based on the proposed integration model show that efficiency penalty varies between 4% and 7% points, which yields lower energy costs than other more mature post-combustion CO2 capture technologies such as the currently commercial amine scrubbing technology. A principal feature of the CaL process at CO2 capture conditions is that it produces a large amount of energy and therefore an optimized integration of the systems energy flows is essential for the feasibility of the integration at the commercial level. As a main novel contribution, CO2 capture efficiency is calculated in our work by considering the important role of the solid-state diffusion controlled carbonation phase, which becomes relevant when CaO regeneration is carried out under high CO2 partial pressure as is the case with the CaL process for CO2 capture. The results obtained based on the new model suggest that integration energy efficiency would be significantly improved as the solids residence time in the carbonator reactor is increased.